Developing an On‐Resin Synthesis of α‐Galactosylceramide‐Peptide Conjugate Vaccines - Dr. Michael A. Meijlink; Dr. Susanna T. S. Chan; Kathryn J. Farrand; Sarah L. Draper; Dr. Oliva K. Burn; Jasmine M. Seifert‐Simpson; Ngarangi C. Mason; Dr. Lisa M. Connor; Prof. Ian F. Hermans; Prof. Gavin F. Painter; Dr. Benjamin J. Compton (ChemistryEurope)
Abstract The covalent attachment of peptide antigens to the NKT cell agonist, α‐galactosylceramide (αGalCer), generates self‐adjuvanting vaccines that prevent and/or eliminate disease in animal models of cancer and infectious disease. To date, the manufacture of these glycolipid‐peptide (GLP) conjugate vaccines utilises an automated solid‐phase process to produce the peptide followed by a manual ‘wet chemistry’ conjugation step. To expedite GLP vaccine manufacture, we sought to develop methodology that enables the attachment of resin‐bound peptide antigen to αGalCer via an amide bond thereby avoiding the need to carry out a separate chemoselective conjugation step. To facilitate this approach, novel analogues of αGalCer incorporating an activated ester spaced by an acid‐resistant, protease‐sensitive linker from either the 6′′‐position or the N‐acyl lipid were synthesised. Reacting these with resin‐bound peptide afforded the conjugate vaccines in good to excellent yields and purity. In vivo testing showed that vaccines incorporating peptide antigen attached via the galactosyl head group induced strong antigen specific CD8+ T cell responses compared to those with antigen attached via the lipid tail and control vaccine manufactured in a stepwise manner.